Non-usage the medical-dental services of the professors of the Universidad Centroccidental Lisandro Alvarado. Venezuela (Revista Venezolana de Salud Pública, 2018)
The purpose of this article is to describe the non-usage the medical-dental services of the professors of the Universidad Centroccidental “Lisandro Alvarado”, throughout a descriptive crossectional study. From a sample of 322 professors estimated by a probabilistic stratified sampling with proportional affixation, an intentional sub-sample of 60 professors that did not use the services was selected. A validated and reliable questionnaire was used to measure the professors’ opinion about those factors that influence the usage of the health services.  The results show: 70.0% of the professors were between 37 and 56 years old; 51.7% and 66.7% are males and marriage, respectively.  Close to a 100% of the professors from the schools of health science, veterinary, business have the academic condition of ordinary and full professors; the profession was related in a high proportion with the school enrolled. On the other hand, 90% had knowledge regarding the medical-dental services; also expressed the primary reasons of the non-usage of the services, among which are: “lack of trust in the health professionals”, “absenteeism of the professionals”, and “inadequate health attention”. Among the conclusions it is important to mention that the majority of professors who did not use the medical-dental services, have knowledge about the functioning of it ; which do not correspond with the demographic and academic profile characteristics. This investigation was sponsored by the CDCHT/UCLA under the code 015-ME-2008.
Keywords: Utilization; services; health; motives